Pengaruh Ekstrak Daun Tumbuhan Mikania micrantha Kunth. (Invasif) dan Cosmos sulphureus Cav. (Non Invasif) Terhadap Perkecambahan Jagung (Zea mays L.) - Ayu Utami Rezki; Suwirmen Suwirmen; Zozy Aneloi Noli (Universitas Andalas, 2018)
The Research about the effects of extract from the invasive plant leaves of Mikania micrantha Kunth. and non-invasive plant leaves of Cosmos sulphureus Cav. on the germination of corn (Zea mays L.) has been conducted in July 2016 in Plant Physiology and Tissue Culture Laboratory, Biology Department, Mathematics and Natural Science Faculty, Andalas University, Padang. The aim of this research was to compare the effect of extract from the leaves of plants M. micrantha and C. sulphureus with several concentrations on the germination of corn. The research used experimental method with Completely Randomized Design (CRD) on Nested, 9 treatments and 4 replications. The treatments were factor A (type of plants, a1= Mikania micrantha and a2= Cosmos sulphureus) and factor B (leaf extract concentration, b0= 0%, b1= 20%, b= 40%, b3= 60%, b4= 80%). The results showed that the extract of the leaves from M. micrantha affected to reduced the fresh weight plants at concentration of 20%, where as in leaf extract of C. sulphureus affected to reduced the fresh weight plants at concentration of 40%.